Aportes de los nuevos enfoques para la conformación de la salud pública alternativa (2011)
ABSTRACT: This article discusses the possibility of a different way from traditional to raise health problems in public health context, answering its guiding question: How the contemporary approaches to public heath help to understand it and size its projection in the coming years? Initially, we will make a brief characterization of conventional public health, in order to show its limitations to answer people’s health problems. Then we enter to the contemporary approaches or tendencies, specifically those developed in the critical school framework, because it’s on them where the approaches that significantly contribute to the health public conformation converge. Among the selected currents we have: the critical theory, the social medicine, the collective health, social determinants of health, the gender approach and the complexity theory, approaches that contribute to a different way of public health working and to have always in mind the importance of the subject in the boarding of health problems. Likewise, the technologic reason directed knowledge must be changed in order to reach the multiculturalism, this accepting other knows as valid to the construction of know.